Responsibilities of a Notary in Making a Will for the Gift of Body Organs Made in His Presence - Susilawati, Susilawati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out and analyze the procedures or procedures for making a will for the gift of bodily organs, to find out and analyze the Notary's responsibility for making a will for the gift of bodily organs made in front of him. Method The approach to the problem used in this research is the Normative juridical approach. The research specifications used in this research are analytical descriptive. The type of research used in this research is normative juridical research using secondary data consisting of primary legal materials which include: Law no. 2 of 2014, Civil Code Law, Law Number 36 of 2009 concerning Health, Compilation of Islamic Law; Secondary legal materials include literature, scientific journals and other supporting documents. Collecting research data using interview techniques and studying library materials. The data analysis method used in this research is qualitative data analysis. The research results show that the procedures or procedures for making a will for the gift of organs have not been explicitly regulated in statutory regulations. In terms of making it, it still refers to Article 1320 of the Civil Code, which states that a will to provide organs can be implemented as long as it complies with the terms of the validity of the agreement. Because there are no specific rules that regulate it, the procedures or procedures will be the same as making a will in general, only the difference in this case is that all the heirs will be present as approving parties and as executors if the person who gave the will has died. In carrying out his office, a Notary must have sufficient legal skills based on a sense of responsibility for respecting the nobility, dignity of his position, values and ethics as stated in the Law on the Position of Notaries which is a guideline for Notaries in carrying out their office.